Pluralisme: Tantangan dan Peluang dalam Proses Dakwah Islam Kontemporer - Abdul Hamid (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2023)
Indonesia is a pluralistic country with a diversity of tribes, races, cultures, and religions. This diversity is known as plurality and is legally recognized through the motto "Bhinneka Tunggal Ika." However, plurality is often misunderstood as pluralism, which is the belief that all religions are equally true. This understanding poses a serious challenge to Islamic preaching, because it leads to relativism of truth and can shake the faith of the people. This research is a library research study with a qualitative descriptive approach. Data were collected from various literatures that discuss the concept of pluralism, the development of its thinking, and the response of preaching to it. The analysis was carried out through interpretation of the ideas of pluralism figures and their impact on the religious understanding of society. The results of the study show that religious pluralism is a doctrinal challenge that has an impact on the understanding of absolute truth in Islam. Three currents of pluralism thought in Indonesia have been identified: first, pluralism that still recognizes the exclusivity of religion; second, liberal pluralism that rejects absolutism; and third, a moderate approach between the two. All three influence the way society understands religious truth. In conclusion, the challenge of today's da'wah is not only in the aspect of social plurality, but also in ideological pluralism that blurs the boundaries of truth. Da'wah must be responsive, dialogical, and solution-oriented without imposing beliefs, but still emphasizing the importance of maintaining the purity of the people's faith from religious relativism